Investigation of thiol/disulfide balance and IMA value before and after training in elite female weightlifters - Sevindi, Tarık (Progress in Nutrition, 2020)
Study Objectives: Doing exercise has certain acute and chronic effects on the body. As part of the metabolic processes, the cells in our body constantly produce free radicals and reactive oxygen species (ROS) during aerobic cellular metabolism, while the antioxidant defense system tries to adapt to this condition. Any change in this balanced state in favor of ROS is considered oxidative stress. Thiol-disulfide balance is a unique, easy, and new method for determining oxidative stress. Ischemia-Modified Albumin (IMA) tissue ischemia is accepted as a new indicator specifically revealing oxidative stress. In the accessible literature in the sports sciences field, no previous studies have been found on the thiol/disulfide balance and IMA value, which have recently been discovered to be among the biomarkers of oxidative stress. Therefore, it was aimed to investigate the thiol/disulfide balance and IMA value in elite female weightlifters before and after training. Methods: The study group of this research was comprised of elite female weightlifters (N= 12) who participated in competitions on behalf of the Turkish National Weightlifting Team, had a training history of at least 5 years, and who were training 5 days a week and above. Oxidative stress parameters (native-thiol, total thiol, disulfide values, and calculated parameters disulfide / native-thiol, disulfide / total thiol and natural thiol / total thiol ratios) and IMA levels of these athletes were evaluated before the training (Group-I) and after the training (Group-II). Results: It was determined that there was no statistically significant difference between Group I and II. Conclusion: It can be mentioned that elite female weightlifters in the study provided metabolic adaptation to the training they performed, and the compensation of antioxidant defense was good. This was interpreted that the participants could continue to the next level of heavier training.